Non-thermal plasma application improves germination, establishment and productivity of Gatton panic grass (Megathyrsus maximus) without compromising forage quality. - Pérez Pizá, María Cecilia; Clausen, Liliana; Cejas, Ezequiel; Ferreyra, Matías; Chamorro, Juan Camilo; Fina, Brenda; Zilli, Carla; Vallecorsa, Pablo; Prevosto, Leandro; Balestrasse, Karina (My University, 2022)
Megathyrsus maximus (Gatton panic) is a tropical grass highly valued both for its use as forage and for its biofuel potential. A major constraint in establishing pastures of this cultivar is the low viability and germination ofseeds and the poorinitialseedling establishment. We used non-thermal plasma (NTP, partially ionised gas) as a novel technology to treat seeds of this grass, aiming to improve their quality (i.e. germination traits). We also followed the performance of seedlings grown from NTP-treated seeds under field conditions by assessing seedling establishment, biomass production and forage quality during the first regrowth period, which is the critical period for pasture establishment. Two NTP treatments were performed through dielectric barrier discharges employing N2 as carrier gas. Non-treated seeds served as the control. Results showed that the viability of NTP treated seeds was, on average, 1.5-fold higher than the control, and that germination energy and germination percentage of treated seeds was superior to the control by 2.1-fold and 2.2-fold, respectively. A field experiment showed that seedling establishment parameters (dynamics of cumulative emergence, emergence coefficient, and weighted average emergence rate) and pasture early productivity (represented by shoot dry matter) were enhanced by NTP treatment (phenolic sheet–polyester film barrier and 3 min exposure), showing 1.4–2.6-fold higher values than the control, confirming the results of the laboratory assays. Although NTP markedly increased the shoot dry matter production of the pasture, which was related to higher tiller population density and greater tiller weight, it did not affect the forage quality of the plants grown in the field. We conclude that NTP technology is suitable to improve seed germination of Gatton panic, in turn leading to improvements in seedling establishment and biomass production under field conditions without compromising forage quality.
Keywords: Early establishment.; Forage quality.; Germination.; Megathyrsus maximus.; Gatton Panic.; Non-thermal plasma.; Pasture productivity.; Seed quality.; Yield components.